Transforming African Higher Education: Precolonial Foundations, Colonial Legacies, and Postcolonial Innovations - Ransom Tanyu Ngenge (Educational Considerations, 2025)
This article critically re-evaluates the evolution of African higher education by tracing its development across three key epochs: precolonial, colonial, and postcolonial. Drawing on over 120 secondary sources–including legal ordinances, policy documents, archival records, and peer-reviewed literature–the article adopts a historical-analytical and decolonial framework to interrogate how education systems were constructed, disrupted, and reimagined over time. It challenges the Eurocentric myth that higher education in Africa was introduced by European colonizers, instead spotlighting rich precolonial traditions such as the Per Ankh in Egypt (c. 2000 B.C.E.), Islamic institutions like Al-Qarawiyyin (859 C.E.) and Al-Azhar (969 C.E.), and the Ethiopian Orthodox education system, which fostered advanced instruction in theology, medicine, astronomy, and literature. The colonial era imposed restrictive education models designed for political control and economic subjugation, marginalizing indigenous knowledge and languages. This legacy persists in postcolonial Africa, where curricula, policies, and institutional frameworks often mirror colonial prototypes. By triangulating sources and comparing colonial education systems across British, French, and Portuguese contexts, the study illustrates both shared and divergent impacts. It concludes that structural reform through the revitalization of indigenous knowledge systems, community-based models, and language-inclusive policies are a pathway toward sustainable, sovereign, and Afrocentric higher education.
Keywords: precolonial education; decolonial perspectives; colonial legacies; Africa